Biografi Dan Pemikiran Filsafat Ibnu Sina: Rekonsiliasi Antara Agama Dan Filsafat Ketuhanan Dan Jiwa - Muhammad Jahar Bulek (Journal of Mandalika Literature, 2025)
Ibn Sina (980-1037) was a scientist besides being an expert in medicine, chemistry and geography, but he was also a prominent philosopher besides Ibn Arabi, Al Kindi, Al Gazali and others. Ibn Sina's philosophical thoughts have had a huge influence on the development of philosophy, from the past to the present.The theory of emannation (emanation), Divine Being, Soul/Nafs, is a fundamental theory, so it has never been overlooked in various philosophical studies, both western and Muslim philosophers. Ibn Sina Islamized western philosophy into a truly Islamic philosophy, thereby breaking down the doubts of some people who assumed that philosophy was not good, conflicted with the science of monotheism and so on.